Sociology of education: Strengthening the role of school committees in Sumber Rahayu Village, Muara Enim regency - Yulasteriyani Yulasteriyani; Randi Randi; Dwi Mirani; Dian Sri Andriani; Yusnaini Yusnaini; Gita Insyanawulan; Yosi Arianti (Universitas Muhammadiyah Magelang, 2023)
This activity aims to internalize the concept of educational sociology theory and strengthen the socio-cultural-educational relationship between the community and the school. This community service activity was carried out in three stages: pre-test, counseling, and post-test. The success of this community service activity can be measured from two achievements, including all series of community service events that went well and smoothly without hindrance, and sociology and school committee materials that were well received and understood by service participants. In addition, the pre-test and post-test results showed an increase in participants' knowledge and experience regarding the concept and theory of school committees.